Protection of Sports Image Rights in Uganda. The Efficacy of the Legal Framework - Saulo Semakula (Uganda Christian University, 2025)
The Bell is Ringing, Aliker.M pg.233 Uganda in Retrospect “…Freedom is an abused word. But real freedom comes with a lot of responsibility. The British did most of the thinking and planning for us….” This is quoted from the Autobiography of the late Martin Aliker, a prominent legislator of Uganda who believed that most of the remnants of the British rule are getting phased out since Ugandans have failed to uphold the standard left behind by the former colonial masters. Looking at Uganda retrospectively, it looks clear more than ever that our legal and legislative power is degenerating tremendously because the laws made today are incredibly hard to logically discuss as some are transplants from other nations. The famed Lord Denning would refer to that as the oak tree from Europe which would never grow the same in Africa like it did elsewhere. The field of Sports in law is emerging and the rights that come with it are undoubtable. It’s important that Uganda should get braced for development and a future of wondrous developments in that area. The machinery of the British man needs to oiled or replaced with new functional implements which can serve as the incentive for the current and future development in sports as arena.
Undergraduate dissertation